When the mirror gets misted up: Modularity and technological change - Furlan, Andrea; Cabigiosu, Anna; Camuffo, Arnaldo (Strategic Management Journal, 2014)
This study investigates how component technological change affects the relationship between product modularity and organizational modularity (the across‐firm mirroring hypothesis). Studying the air conditioning industry, we show that the across‐firm mirroring hypothesis does not hold for technologically dynamic components and the associated supply relationships. In this case, the mirror gets “misted up” with buyers and suppliers having recourse to information sharing even in the presence of highly modular components. Our study contributes to the debate on the organizational implications of modularity and its ramifications for the theory of the firm . Copyright © 2013 John Wiley & Sons, Ltd.